Avaliação de durabilidade quanto à carbonatação de concretos com incorporação de resíduo cerâmico - Morato, Renata Cristina de Oliveira (Universidade Federal Rural do Semi-Árido, 2017)
The current scenario has motivated the research for the reuse and recycling of waste as non-concrete aggregates and as pozzolanic materials, from a new disposal, reduce costs, improve mechanical properties, performance and durability. Among these residues, the Red Ceramic Residues (RCV), from tiles, bricks and blocks, which after crushing, produced with pozzolanic commodities, stand out. This study analyzes and compares the durability of conventional concrete and concrete with ceramic waste as a penetration of CO2 particles in urban environment. A total of 44 proof bodies (PB’s) were made, of which 22 PB’s of conventional concrete 0% of cement substitution per RCV and 22 concrete PB’s with 25% cement substitution for RCV, both with A/C factor of 0.65, Followed by the test trials: drop test, absorption and porosity, compressive strength and durability test for carbonation by phenolphthalein sprinkling. At all ages the samples with addition of residue presented larger fronts and carbonation, also indicated a considerable increase of porosity and consequent loss of compressive strength when compared to the reference trait. Unsatisfactorily proving the replacement of cement by RCV, as well as the properties of concrete.
Keywords: Adição Mineral; Mineral Addition; Cerâmica Vermelha; Red Ceramics; Concreto Sustentável; Sustainable Concrete; Dióxido de Carbono; Carbon Dioxide; ENGENHARIAS::ENGENHARIA CIVIL